Early Neurological Deterioration following acute stroke: association with reperfusion therapies and National Institutes Of Health Stroke Scale score - Yu, Tony Bing; Lee, Cameron; Mallah, Mohammed; Belo, Caroline Domingos; Uribe Mz Recaman, Maria Lucia; Noui, Yassine; Bayhonan, Samantha; Sari, Beatrix; Mah, Yee-Haur (Frontiers in Stroke, 2025)
Early Neurological Deterioration (END) following acute stroke is associated with worse long-term functional outcomes. END is poorly defined and its relationship to reperfusion therapies is not fully understood. NIHSS is commonly used to risk-stratify and identify END following acute stroke however its relationship to END is relatively unexplored. The electronic health record of 933 stroke patients admitted to the Hyperacute Stroke Unit at King's College Hospital in 2022 were manually reviewed for END up to 14-days post stroke to: (1) characterize etiology and risk factors associated with END following acute stroke, and (2) evaluate the association between END, reperfusion therapy and NIHSS. Age, sex and co-morbidity were not associated with END, whereas reperfusion therapy was associated with greater END risk. Admission NIHSS was associated with END in those receiving conventional therapy alone, however, was not associated with END in those receiving reperfusion therapy. For those receiving IVT or EVT, the change in NIHSS at 24-hours was associated with END whereas admission NIHSS was not. In patients with a stable NIHSS 24-hours post stroke, there remained a greater than 10% risk of END. In conclusion, demographic factors and co-morbidity appear less important in determining END risk than stroke severity and treatment type. Admission NIHSS had limited association with END risk in those undergoing reperfusion therapy whereas the change in NIHSS at 24-hours was useful. NIHSS alone appears insufficient in its sensitivity to END to act as a risk-stratification tool, as significant END risk remains in those with stable or improving NIHSS.